2005
DOI: 10.1055/s-2005-865852
|View full text |Cite
|
Sign up to set email alerts
|

Polyembryony and Apomixis in Eriotheca pubescens (Malvaceae - Bombacoideae)

Abstract: Apomixis and adventitious polyembryony have been reported for several species of Bombacoideae, including Eriotheca pubescens, a tree species of the Neotropical savanna (Cerrado) areas in Brazil. However, the origin of polyembryonic seeds and their importance for the reproduction of the species remained to be shown. Here, we analyzed the early embryology of this species to establish the apomictic origin of extranumerary embryos. We also observed the geographic distribution of polyembryony in E. pubescens, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 39 publications
9
61
0
9
Order By: Relevance
“…Mas de maneira geral a espécie é autocompatível e não apomítica. A possibilidade de apomixia via pseudogamia, como ocorre em outras plantas lenhosas de cerrado (Costa et al 2004, Mendes-Rodrigues et al 2005, não pode ser afastada. No entanto, a frequência de tubos polínicos e fertilizações nos pistilos resultantes de autoplonização espontânea indicam que a contaminação natural dos pistilos em infl orescências ensacadas é sufi ciente para explicar a frutifi cação obtida neste tratamento.…”
Section: Discussionunclassified
“…Mas de maneira geral a espécie é autocompatível e não apomítica. A possibilidade de apomixia via pseudogamia, como ocorre em outras plantas lenhosas de cerrado (Costa et al 2004, Mendes-Rodrigues et al 2005, não pode ser afastada. No entanto, a frequência de tubos polínicos e fertilizações nos pistilos resultantes de autoplonização espontânea indicam que a contaminação natural dos pistilos em infl orescências ensacadas é sufi ciente para explicar a frutifi cação obtida neste tratamento.…”
Section: Discussionunclassified
“…Morphological anomalies, brood competition inside the seed and seedling competition during establishment may affect the turnover of embryos into seedlings (Hotchkiss et al, 2008;Mu et al, 2010;Uma Shaanker and Ganeshaiah, 1997). Brood competition would be due to the limited amount of resources allocated to each seed and may be evinced by the reduction of mean embryo mass with the increase on embryo number per seed (Mendes-Rodrigues et al, 2005). Anomalies on size and morphology of cotyledons are related with competition for space and, although they may not affect the turnover of these embryos into seedlings, in more severe cases they do impair seedling establishment (Mendes-da-Glória et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Reported for at least 115 flowering plant families and very common and widespread among the Angiosperms (Carman, 1997), polyembryony has been studied and described for temperate weeds (Asker and Jerling, 1992;Naumova, 1992), and for some families of tropical woody species as Bignoniaceae (Costa et al, 2004), Malvaceae (Mendes-Rodrigues et al, 2005) and Melastomataceae (Goldenberg and Shepherd, 1998; Abbreviations: MENS, mean embryo number per seed; MSNS, mean seedling number per seed; PSP, polyembryonic seed percentage; EC, embryonic class.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta in 1996 [81] reported in guggul (Commiphora wightii) the occurrence of apomixis not pseudogamous (development of an embryo only from maternal chromosomes after activation of the egg by a sperm: sperm penetrates the egg, causes division, but there is no effective fertilization), nucellar PE and autonomous endosperm formation suggesting that plants have reproductive and survival strategies in the absence of male plants, but in the presence of males, sexual reproduction can occur. Moreover, in 2005, Mendes-Rodriguez [82] studied Eriotheca pubescens, which presents apomixis and adventitia polyembryony, found that in seeds, the zygote became a sexual embryo simultaneously with apomictic adventitious embryos that developed from nucellus cells. The adventitious embryo developed more rapidly than sexual ones, but they are morphologically similar so that 44 days after anthesis it was impossible to distinguish the sexual from the apomictic embryos.…”
Section: Polyembryony and Apomixesmentioning
confidence: 99%